Obtención de bacterias endófitas del tomatillo (lycopersicum pinpinelifoluim l.) como promotoras de crecimiento vegetal - Plaza Avellán, Ignacio Enrique (2020)
This research work was carried out in the Molecular Biology laboratory of the Veterinary Medicine degree at ESPAM MFL (Escuela Superior Politécnica Agropecuaria de Manabí “Manuel Félix López”), with the aim of obtaining endophytic bacteria from tomatillo as growth promoters vegetable. The work had two phases: the first was in the laboratory, consisting of the isolation, characterization and in vitro evaluation of endophytic bacteria under stress conditions, which allowed obtaining four bacteria (CaP41R-5, ChoP3R-5, QuiP2R5-8 and EstP4T6) as promoters of plant growth. The second phase consisted of determining the plant growth promoting effect of the isolated and selected bacteria in tomato plants. The factors under study were the bacterial endophytic isolates and types of substrates (Conventional and organic), the substrates were sterilized, the experimental units were nursery pots with tomato seeds of the Margot F1 variety, the variables evaluated were: plant height (cm) , root length (cm), fresh weight aerial part and root (g) and dry weight aerial part and root (g). It is concluded that the evaluation of endophytic bacteria as promoters of plant growth in tomato plants acted equally, on the evaluated variables; although better behavior was observed in conventional soil, it is probably due to the fact that there could be a greater amount of nutrients for the plant because it is an area with greater exploitation, unlike organic soil. However, these tests are promising and it would be necessary to continue carrying out studies that allow knowing the response of the plant to these microorganisms in productive environments.